Direct angiotensin II type 2 receptor stimulation acts anti-inflammatory through epoxyeicosatrienoic acid and inhibition of nuclear factor κB - Rompe, Franziska; Artuc, Metin; Hallberg, Anders; Alterman, Mathias; Ströder, Katja; Thöne-Reineke, Christa; Reichenbach, Anne; Schacherl, Jens; Dahlöf, Björn; Bader, Michael; Alenina, Natalia; Schwaninger, Markus; et al. (Hypertension, 2010)
Angiotensin II type 2 (AT2) receptors can be regarded as an endogenous repair system, because the AT2 receptor is upregulated in tissue damage and mediates tissue protection. A potential therapeutic use of this system has only recently come within reach through synthesis of the first selective, orally active, nonpeptide AT2 receptor agonist, compound 21 (C21; dissociation constant for AT2 receptor: 0.4 nM; dissociation constant for angiotensin II type 1 receptor: >10 000 nM). This study tested AT2 receptor stimulation with C21 as a potential future therapeutic approach for the inhibition of proinflammatory cytokines and of nuclear factor κB. C21 dose-dependently (1 nM to 1 μmol/L) reduced tumor necrosis factor-α-induced interleukin 6 levels in primary human and murine dermal fibroblasts. AT2 receptor specificity was controlled for by inhibition with the AT2 receptor antagonist PD123319 and by the absence of effects in AT2 receptor-deficient cells. AT2 receptor-coupled signaling leading to reduced interleukin 6 levels involved inhibition of nuclear factor κB, activation of protein phosphatases, and synthesis of epoxyeicosatrienoic acid. Inhibition of interleukin 6 promoter activity by C21 was comparable in strength to inhibition by hydrocortisone. C21 also reduced monocyte chemoattractant protein 1 and tumor necrosis factor-α in vitro and in bleomycin-induced toxic cutaneous inflammation in vivo. This study is the first to show the anti-inflammatory effects of direct AT2 receptor stimulation in vitro and in vivo by the orally active, nonpeptide AT2 receptor agonist C21. These data suggest that pharmacological AT2 receptor stimulation may be an orally applicable future therapeutic approach in pathological settings requiring the reduction of interleukin 6 or inhibition of nuclear factor κB.